Characteristics of The Ability of Physics Concept in Enrichment Teaching Materials of Natural and Mineral Resources (NMRs) Literacy - Rochman, C.; Nasrudin, D.; Muslim, M.; Hermita, N. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
This study is aimed at describing the characteristics of basic physics concepts in materials of science literacy enrichment of natural and mineral resources (NMRs) prepared by students of Physics Education Department, Universitas Islam Negeri Sunan Gunung Djati Bandung. The method of data collection for scientific literacy ability of NMRs is obtained from the description of NMRs, results of describing the enrichment materials of NMRs process, the basic concepts of physics, and context as well as attitudes of students towards NMRs through paper enrichment materials. This study was conducted to 15 documents ofÂ enrichment materials made by students. The study concluded that: (1) characteristics of studentsâ€™ ability to describe the physics concepts in literacy enrichment materials NMRs show variation; (2) the ability of describing concept of fundamental physics in five NMRs groups being investigated shows a low gains. The study recommends that the application of material needs developing and teaching media literacy enrichment and physical sciences should have more contextual NMRs for secondary, high school and undergraduate students.